Research progress on the uptake and transport of antimony and arsenic in the soil-crop system - He, Jianyang; Yang, Ke; Wang, Sheng; Li, Yingmei; Bao, Li; Zhang, Naiming (Frontiers in Plant Science, 2025)
Antimony (Sb) and arsenic (As) are homologous elements that pose significant threats to the ecological security of soil-crop systems and the health of agricultural products due to their co-contamination. Although they share similarities in plant uptake and translocation, significant knowledge gaps remain regarding the uptake mechanisms of Sb, especially Sb(V), and its interactions with As. This review systematically summarizes the sources, chemical speciation, and bioavailability-regulating factors (e.g., pH, redox conditions, microbial communities) of Sb and As in soil-crop systems, focusing on their uptake pathways, translocation characteristics, and synergistic or antagonistic effects under co-contamination. Comparative analyses suggest that As(V) is taken up through phosphate transporters, whereas the transport mechanism of Sb(V) remains unclear. Under co-contamination, As may enhance Sb accumulation by altering membrane permeability; however, differences in their translocation efficiency and speciation transformation lead to antagonistic effects. Additionally, soil physicochemical properties and plant species significantly influence Sb-As toxicity responses. The detoxification mechanisms of hyperaccumulators (e.g., Pteris vittata) offer novel insights for remediation technologies. By integrating multidisciplinary findings, this review identifies key challenges in co-contamination research and provides theoretical foundations for farmland remediation and risk management based on bioavailability regulation.